Estimation method of heating value properties on variations of alcohol-gasoline blends and volume percentages / Muhammad Syarifuddin Mohamed Zaharin ...[et al.] - Mohamed Zaharin, Muhammad Syarifuddin; Abdullah, Nik Rosli; Badrulhisam, Najmi Haziq; Hamzah, Fazlena; Majeed Ali, Obed (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Heating value has been one of the important properties of gasoline surrogate fuel being investigated for thermal conversion system inside combustion cylinder. Alternative fuel yielded from biomass is expected to have lower energy content than baseline fuel (gasoline), as several factors were analysed such as molecular structure and carbon contents. Qualifying fuel's heating value properties can serve the researchers who work on different alternative fuels to indicate the fuel suitability for spark-ignition engines according to fuel standards. This research work was conducted to study the effects of alcohol blends (methanol, ethanol and iso-butanol) at different volume percentages (0-25%) with an interval of 2.5% on the heating value of gasoline fuel. A non-linear relationship was observed for heating value of each fuel blend generated from statistical polynomial regressions with the highest order of two. Polynomial equations derived were expected to be highly accurate in estimating the properties of heating value of the fuel blends as the coefficient of determination obtained for methanol, ethanol and iso-butanol blends were 0.9445, 0.9691 and 0.692, respectively. Analysis based on the percentage error was done using average absolute error and average bias error with those blends producing lower than 2% error. The estimation model is suggested to be used as it produces highly accurate and precise results for the alcohol-gasoline blends.